EVALUASI KINERJA KEDAI PESISIR âMITRA JALADRIâ DI KECAMATAN KRETEK KABUPATEN BANTUL - , YAPENTRIADI NUGRAHA; , Ir. Hery Saksono, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main aims of this research were to know the performance of Kedai Pesisir in the managerial aspect, problems faced by the board or the manager, and to know public or fishersâs perception againtKedai Peisir Mitra Jaladri. Data was collected by observation, interview with guided questionnaire, and in-depth intervewing with key informan. Purposive sampling method was applied to determine respondents. The study indicated that 44% respondents felt the benefits of Kedai Pesisir, while 56% respondents did not feel the benefits. Managerial processes in Kedai Pesisir âMitra Jaladriâ is running unprofessional and have not been able to serve fishers in Bantul Regency overall. The problems faced by managers is low discipline of the board or employees. The location away from the center of fishery activity and limited stock gear makes fishers in The West Bantul Regency almost never access Kedai Pesisir. Currently, Kedai Pesisir evolving toward fulfillment of basic needs and support the tourism sector.